Expression of beta 2 integrins on blood leukocytes of cows with or without bovine leukocyte adhesion deficiency - Cox, E.; Mast, J.; MacHugh, Niall D.; Schwenger, B.; Goddeeris, Bruno M. (Elsevier, 1997)
Peripheral blood leukocytes of 11 normal cows, 7 cows heterozygous and 2 heifers homozygous for bovine leukocyte adhesion deficiency (BLAD) were analysed by flow cytometry for the intensity of their B2 integrin expression (LFA-1 (CD11a/CD18), CR3 (CD11b/CD18) and CR4 (CD11c/CD18)). BLAD-homozygotes revealed no or a very weak expression of the B2 integrins and had a 10-fold and 4- to 5-fold increase in absolute number of neutrophils and monocytes, respectively, whereas the absolute number of lymphocytes remained normal. The mean fluorescence intensity (MFI) of the B3 integrins (CD18) in heterozygous animals was 56 to 90 percent of this in the normal cows (MFI between 14 and 512). The difference in the expression level was most pronounced for LFA-1 on the small culuster of lymphocytes with the highest MFI for LFA-1. Repeated analysis and phorbol myristate acetate stimulation revealed that the LFA-1 expression on this high-expressing cell population of the peripheral blood allowed a ready identification of BLAD-heterozygotes by flow cytometry.